Introducción a IPv6 - Salazar Vega, Edwin (2019)
As is publicly known, the central pool administered by IANA IPv4 is exhausted in February 2011, this means that the global system of Internet addresses has been exhausted. In that sense, it is necessary and mandatory to understand how IPv6, the new internet protocol, and its coexistence with IPv4. We also analyze and decide whether to migrate to IPv6 transition mechanisms which we use, among others. Simply put: It's time to prepare for the coexistence of two Internet protocols, IPv4 and IPv6.